BRICS AGAINST HEGEMONY OF THE UNITED STATES DOLLAR IN THE INTERNATIONAL MONETARY SYSTEM - Firdaus, Najmi; Widayanto, Sulistyo; Indrayani, Irma (Universitas Nasional, 2023)
This study aims to examine the indications of a new currency project which is planned to be announced at the BRICS Summit in South Africa2023. The BRICS countries now account for 40% of the global population and a quarter of global GDP. PUse of Yuan has increased over recent years, accounting for 7% of global foreign exchange trading. While the US dollar continues to play a large role in the international financial system, including serving as the leading global reserve currency. US dominance is increasingly facing challenges from oil-producing countries, including Iran, andalsoWashington's longtime ally Saudi Arabia which announced that it would consider selling oil in currencies other than Dollar. The research uses the theory of International Monetary System and Counter Hegemony in understanding the problems that occur. This research uses a qualitative approach to explain a phenomenon in depth and examines more to the substance of the meaning of the phenomenon.The findings of this research are on the attitude of each BRICS member country, that although BRICS has a discourse for the global financial system, but no country seems to seriously intend to de-dollarize or make a real effort to find an alternative currency to replace the US dollar. The goal that is in the common interest of BRICS is not to replace, find an alternative to the dollar, or even for the purpose of lowering the value of the US dollar. The common goal is to control hegemony so that the US cannot arbitrarily exercise its political power for unilateral economic and military interests.